Modeling as an effective management tool for the integrated regional development (Revista de Investigaciones Universidad del Quindío, 2022)
Ensuring sustainable territorial development is one of the key tasks for developing regional industries and increasing the level of food security of the regions and the country in general. The solution to the problem of developing and implementing a competitive mechanism for territorial development should be based on the principles and methods of modern strategic territorial-sectoral planning with a focus on the maximum use of the resources of the existing local potential. This study analyzes modeling as an effective management tool for integrated regional development. To that end, approaches based on constructing multivariate regression models are utilized. Based on the results,  the main problem of management systems for the integrated territorial development is associated with an incorrect assessment of their starting capabilities, which results in the low performance of the implementation mechanism. A reliable methodological basis here can be an approach to managing territorial development using a system of linked indicators that consider more than just the parameters of social development. The list of priority areas (blocks), which should serve as a fundamental basis for developing concepts for the integrated development of regions, must include natural and climatic, technical and technological, infrastructural, and marketing characteristics.Keywords: regional development, regional competitive potential, modeling, integrated development .
Keywords: regional development; regional competitive potential; modeling; integrated development